Դավիթ Դվնեցու վկայաբանությունը և նրա պատմագիտական արժեքը - Ազատյան, Շավարշ
The long-term Persian-Arabic rule had a profound impact on Armenian hagiographical literature. The persecutions and ideological pressures of the conquerors compelled the Armenian clergy to devise suitable solutions. In these circumstances, separate martyrdoms were created concerning the conversion of representatives of the conquered peoples. Surhan was also one of the Armenian heroes who was named David after being baptised. It can be recorded that the author of the Martyrdom fulfilled the order of the bishop of Amatunyatsʻ and the Mamikonian princes. This is confirmed by the relic symbols found in the Martyrdom, including the cross and the spear. David's Martyrdom, with its distinctive allegorical structure and plot, nevertheless conveys authentic information about the period of Arab invasions and dominions. The Islamic challenge compelled the author to present David's Martyrdom in a more convincing manner, showcasing novel religious plots and spatial perceptions. The Martyrdom contains numerous references that provide invaluable insights into the economic and political life of Armenia in the second half of the 7th century. The data on the pre-Islamic legal system, in particular the rule of Hudud (Ḥudūd Allāh [God's boundaries]), are also noteworthy.
Keywords: Հայոց պատմություն